Saúde global, biopolítica e neoliberalismo: uma análise arqueogenealógica das relações entre saúde e economia na Pandemia de Covid-19 - Dumaresq, David Mendes (2021)
This paper investigates the performance of a neoliberal rationality of government from the field of Global Health. Our option for the archeogenealogy as an analytical procedure is allied to an intense dialogue with the conceptual contributions brought by the work of the French philosopher Michel Foucault and authors whose analyses are in affinity with it. The research starts from the recognition, on the one hand, of a discursive formation that enunciates the strategic priority of health regarding the public administration of the countries in this delicate moment, and, on the other hand, of a discursive formation that affirms that the economic sphere is the fundamental key to unblock an appropriate public management of the pandemic phenomenon - also indicating a third formation that proclaims the conciliation between the two spheres. Armed with these provisional groupings, and perceiving their action in the critical moment of confronting the pandemic of COVID-19 in Brazil, this dissertation is guided by the following research problem: how is it possible to establish a radical opposition between a position in defense of life and a position in defense of the economy in a society in which we witness a radical fusion between health and economy? With this investigative horizon, we elected as materiality to be analyzed three practices in Global Health that will serve as points of support for our discussion: 1) the Disability Adjusted Life Years (DALY) indicator, an important and influential metric produced at the end of the 20th century that has the purpose of quantifying the economic burden attributed to diseases and risk factors around the globe; 2) the Framework Convention on Tobacco Control (FCTC), the first international public health treaty in the history of the World Health Organization (WHO); and, finally, 3) the Focused Protection strategy, proposed by three epidemiologists as an alternative to strict social isolation policies in confronting the pandemic of COVID-19 around the world. We understand DALY not only as a mere example, but as a materialization and an important signpost of the specific kind of governance practices and calculative management of life that are at stake in neoliberal rationality, especially when it is inscribed in the field of health policies. We have therefore allocated two chapters of the research to DALY - one for its presentation (Chapter 2) and the other for its analysis (Chapter 3). The two other Global Health strategies are presented and analyzed in Chapter 4 and, at that point, we will position them in relation to the aforementioned discursive formations (pro-life front vs. pro-economy front) - which will allow us to broaden, deepen, and concretely flesh out our research problem, giving it a possible direction that will be presented at that time. In the last analysis, we argue with this research that, even though the practices in Global Health have very diverse characteristics in their procedures, objectives, andeffects, they seem to share the same logic of neoliberal government in the concrete conduction of their projects.